Navigating Trends and Ecological Sustainability Needs in Germany and Europe’s ICT Industry - Adu, Lotta; Aslan, Tugana; Gorlova, Katerina; Thesen, Manuel (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
<span class="NormalTextRun SCXW49705595 BCX0" data-ccp-charstyle="normaltextrun" data-ccp-charstyle-defn=""ObjectId":"ac0262f4-8a9e-5820-b908-2d943c5f7113|1","ClassId":1073872969,"Properties":[469777841,"Calibri",469777842,"Arial",469777843,"SimSun",469777844,"Calibri",469769226,"Calibri,Arial,SimSun",268442635,"22",469775450,"normaltextrun",201340122,"1",134233614,"true",469778129,"normaltextrun",335572020,"1",469778324,"Default Paragraph Font"]">The Information and Communication Technology (ICT) industry significantly impacts the environment across various life cycle stages, including material sourcing, energy use, and waste. To mitigate these effects, the German Ministry for Education and Research established the Competence Center Green ICT @ FMD, focusing on applied research to reduce the environmental footprint of ICT technologies. This paper identifies five emerging areas within the microelectronics sector that are key for ecological sustainability and the economic future in Germany and Europe to address the negative environmental impact of the rapidly growing demand of ICT: (i) Circularity in microelectronics, (ii) Green data centers, (iii) Green power electronics, (iv) Green quantum technologies, and (v) Green procurement and supply chains. These areas were identified through a systematic approach involving surveys, expert interviews, roadmap analysis, literature review, and market research. Criteria such as geographical relevance, time-related relevance and leverage were used to assess the feasibility of each area. Circularity in microelectronics addresses resource efficiency and product lifetime extension, while green data centers focus on hardware, software, and infrastructure optimization to reduce environmental impact. Green power electronics aims to enhance energy efficiency in critical sectors like electromobility and data centers. Green quantum technologies explore innovative applications in sensors and chemical processes, and green supply chains emphasize reducing CO2 emissions throughout value chains.